Burkina Faso : Poverty Reduction Strategy Paper; Progress Report. (IMF Staff Country Reports; Country Report ;, 2005)
The Poverty Reduction Strategy Paper (PRSP) on Burkina Faso explains the status of the PRSP, implementation, and key strategic areas. Actions to reduce the vulnerability of the poor have had more noticeable impact, as have actions to increase employment opportunities and promote income-generating activities. Efforts to improve governance have led to major reforms in the justice system and fiscal management, as well as continued action to improve administrative management, strengthen public security, and further decentralization. The government expects the various development partners to provide more resources and greater assistance for the budgetary support mechanism.